2008
DOI: 10.1063/1.2978390
|View full text |Cite
|
Sign up to set email alerts
|

A simple and flexible thin film evaporating device for energetic materials

Abstract: A thin film evaporation device has been developed to prepare energetic materials at atmospheric pressure. The device is intuitive, simple, and easy to manipulate. The application of the device is demonstrated for pentaerythritol tetranitrate but can be extended to other explosives and organic materials that have low saturation pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Weeks et al [103] reported a simple apparatus for thermal vapor deposition under atmospheric pressure instead of vacuum, which is applicable to substances such as PETN. A very sensitive quartz crystal microbalance was used to monitor the deposition process, and a film growth rate as low as 0.1 Å s À 1 was measured.…”
Section: Vapor Deposition (Physical and Chemical)mentioning
confidence: 99%
“…Weeks et al [103] reported a simple apparatus for thermal vapor deposition under atmospheric pressure instead of vacuum, which is applicable to substances such as PETN. A very sensitive quartz crystal microbalance was used to monitor the deposition process, and a film growth rate as low as 0.1 Å s À 1 was measured.…”
Section: Vapor Deposition (Physical and Chemical)mentioning
confidence: 99%
“…The roughness of these substrates was measured using an atomic force microscope (AFM), and all data were below 5 nm rms. Organic thin films were deposited by thermal evaporation at atmospheric pressure [41], high vacuum [42], or with spin coating [7]. Organic thin film thicknesses ranged from 30 nm to 3 lm.…”
Section: Organic Thin Film Formationmentioning
confidence: 99%
“…Great efforts have been made to generate consistent vapors of various compounds for landmine determination [215], environmental chemical monitoring [216], explosives detection [217][218][219][220] and sensor calibration [221] throughout the past decades. One technique such as Controlled Odor Mimic Permeation Systems (COMPS) uses a thin plastic film to release vapors generated from the solid compounds into the headspace at a fixed rate [11,222].…”
Section: Microdrop Generation Technologymentioning
confidence: 99%